CARBON DYNAMICS: EVER GOING TO STOP INCREASING? - Hartunga, Katalin (European Scientific Journal, ESJ, 2014)
The purpose of the study was to mimic carbon dynamics in the atmosphere and to simulate the change of carbon under different versions of the base model. The simulation contains namely three stocks the CO2 in atmosphere, - in biosphere and - emission from fossil fuels. The assumption is that ocean carbon uptake and outflow cannot be directly influenced by policy makers. There are factors influencing carbon in- and outflow which are the rate of respiration, the decomposition, the area of forests, the net primary production, the deforestation, the assumed growth rate of fossil fuel demand and the saturation of consumption. The study unveils the dynamic of this process by applying system thinking and uses AnyLogic 6.9.0 version software for modeling system dynamics. The model originally elaborated by Hartmut (1994). The software facilitates to forecast the change of carbon if fossil fuel consumption will saturate and if deforestation will be stopped. The overall aim was to create a simulation to see the sensitivity of the ecosystem and try to eliminate climate change due to the escalation of carbon. The results of this analysis can be used to identify the necessary changes to stop carbon growth in the atmosphere. The anticipated outcome of this simulation is to set up the original model and to create three versions of the base model. The findings may be useful for decision makers in the field of sustainability, biomass power plants operators or for energy and environment strategy managers.